VOLATILITAS HARGA SAHAM PADA SEKTOR PERTANIAN DI INDONESIA - Dhistianti Mei Rahmawan Tari (Jurnal Manajemen Bisnis Krisnadwipayana, 2021)
This study aimed to analyze the influence of trading volume, dividend yield, debt to equity ratio and interest rate to stock price volatility companies listed on the Indonesia Stock Exchange in the period of year 2017-2019. The populations of this study are all agriculture companies listed in Indonesia Stock Exchange (IDX) in the period of year 2017 to 2019. It obtained only seven companies samples from total population with technique purposive sampling method. The data analysis technique used is smartPLS software. The results showed that the volatility of the stock price can by earning per share, net profit margin, price to book value, price earning ratio, return on equity, and trading volum,. Net profit margin, price to book value and trading volume have significant effect on stock price volatility while the rest of variables stated otherwise.